Comparação das respostas cardiorrespiratórias ao exercício submáximo de alunos de Educação Física atletas e não atletas - Gomes, Fabrícia Barbosa (2017)
Introduction: Cardiorespiratory fitness is one of the most important variables in the evaluation of physical fitness. Although there are studies addressing cardiorespiratory fitness among adolescents, few evaluated these submaximal responses (LAV and RCP) among 14- and 15-year-olds using direct measures. Objective: To test the hypothesis that students who participate in EF classes together with a systematic training in their counter-school shift will have better conditioning at submaximal levels of the exercise when compared to those who only do EF classes. Methods: 45 students with mean age of 14.6 ± 0.5 years, 25 boys, 16 athletes (GA) and 9 non-athletes (GNA) and 20 girls (GA = 8, GNA = 12) were submitted to CPTE. The variables evaluated were VO2máx, %VO2LAVmáx, HRmáx, % HRmáx, RTR in both submaximal thresholds. To test the normality of the data the Shapiro Wilk test and the non-parametric Mann-Whitney test were used. To compare the means of CPET between the groups, the Univariate Variance Analysis - general linear model (ANCOVA) was used to determine the differences between groups controlling for standard demographic variables such as maturation and percentage of body fat (%GC). Results: the results obtained in the comparison between the male groups revealed that there were differences in the submaximal variables (VO2LAVmáx, %VO2LAVmáx and velocityLAV, VO2RCPmáx, and velocityRCP). The data obtained in the comparison between the female groups revealed that GNA presents values of metabolic and cardiac variables very close to the GA suggesting that EF classes have promoted the maintenance of the aptitude of these students, except for the speed obtained in the CPTE in both thresholds that are presented higher for GA. Conclusion: EF classes combined with the systematized training in the counter shift of adolescent students may have an effect on cardiorespiratory fitness in the submaximal parameters of male athletes. Regarding the female gender, the groups presented no differences regarding the submaximal metabolic cardiorespiratory responses, except for the velocity obtained in the CPTE.